Different Analysis of β-Cell Dysfunction as Fasting Glucose Progresses in Obese and Nonobese Newly Diagnosed Type 2 Diabetic Patients. (28th October 2019) - Duan, Yan; Sun, Xiaomeng; Liu, Jia; Fu, Jing; Wang, Guang
Abstract : Aims/Introduction . This study is aimed at (1) investigating the change of β -cell dysfunction as baseline fasting glucose progresses in newly diagnosed patients with T2DM and (2) finding whether body mass index (BMI) has different degrees of impact on insulin secretion as baseline fasting glucose progresses. Materials and Methods . 661 patients with newly diagnosed T2DM were enrolled in the present study. A 75 g oral glucose tolerance test was used to calculate HOMA- β, HOMA-IR, early-phase insulin secretion index (EISI, calculated as Δ I30 / Δ G30 ), and area under the insulin releasing curve (AUCI0-180 ). Patients were divided into low, medium, and high FBG groups. Each group was further divided into lean, overweight, and obese subgroups according to BMI. Results . A decrease of EISI and HOMA- β and an increase of HOMA-IR were shown among different FBG groups significantly. In the medium FBG group, AUCI0-180, EISI, HOMA- β, and HOMA-IR in obese patients were higher than those in lean and overweight patients. In the low and high FBG groups, AUCI0-180, HOMA- β, and HOMA-IR in obese patients were higher than those in other subgroups. BMI was positively associated with high EISI in the medium FBG group but failed to yield a significant association with EISI in the low and high FBG groups. Conclusions . During the progression of baseline FBG, β -cell dysfunction and insulin resistance worsened. As FBG increased, increased BMI had a positive influence on β -cell dysfunction in all FBG groups. The independent factors that correlated to EISI differed with the increasing of baseline FBG.